Implementation of Islamic Religious Education Values in Stunting Prevention Programs - Nur Kholis; Dewi Septiana; Muhammad Yusuf; Novita Herawati; Joni Pratama; Ade Rifani Ardian (Attractive : Innovative Education Journal, 2026)
Stunting is a chronic nutritional problem that requires a holistic approach to its management. Kampar Regency, with 89.12% of its population being Muslim, has successfully reduced the prevalence of stunting from 1,300 children to 571 children through the integration of Islamic religious education values in its prevention programs. This study aims to describe the implementation process of Islamic religious education values in stunting prevention programs in Kampar Regency, identify inhibiting factors in implementing Islamic religious education values, and propose strategies to overcome barriers in implementing Islamic religious education values in stunting prevention programs. The research used a qualitative descriptive approach with data collection techniques through in-depth interviews with 6 key informants, observations of 5 stunting prevention programs namely Gadih Ancak, Ocu Mapan, Gemarikan, Mobile Posyandu, and BAAS, as well as documentation. Data analysis used the Miles and Huberman model with stages of data reduction, data presentation, and conclusion drawing. The implementation of Islamic religious education values was manifested through three main dimensions: aqidah values that teach that maintaining children's health is Allah's trust, sharia values that apply the concept of halal-thayyib in providing nutritious food, and akhlaq values that form social solidarity through the BAAS program. The religious approach increased community participation from 60-70% to 85-90%. Inhibiting factors include limited religious understanding among health workers, differences of opinion among religious scholars, and the absence of formal regulations. Strategies to overcome barriers include cross-sector training for human resources, strengthening cross-sector coordination, developing formal regulations, and standardizing health da'wah materials. The integration of Islamic religious education values has proven effective in increasing community motivation and participation in stunting prevention programs. The Kampar Regency model can serve as a reference for best practices with improvements in formalization and standardization aspects.